Analysis the Impact of Profitability, Liquidity, Leverage and Company Size on Dividend Policy - Besnedi Abrar; Riandra Ghazyla; Dila Arisandi (Universitas Trisakti, 2017)
This study aims to determine the impact of financial ratio and company size on dividend policy. Multiple linear regression is used to identify the relationship between the independent and dependent variables. The sampled data was taken from consumer goods manufacturing companies listed on Indonesia Stock Exchange for the period 2015-2017. The result of this study indicated that financial ratios variable proxied by profitability and leverage ratios had a significant impact on dividend policy, while the other variables liquidity and company size had an insignifiant impact on dividend policy.